Factors Affecting the Adoption of PromptPay among Online Micro-retailers in Thailand - Thavorn, Jakkrit; Terasirisin, Noppamas; Klongthong, Worasak (APMBA (Asia Pacific Management and Business Application), 2020)
Anticipating dramatic growth in the country’s e-commerce market, Thailand’s government initiated the PromptPay system for online retailers. However, many consumers have not yet signed up for the service, and small vendors tend not offer PromptPay as a payment option. This study aimed to understand the factors that affect online retailers’ intention to utilize PromptPay when selling their products on social media. An online questionnaire was used to collect data for quantitative analysis from 247 respondents who were individual merchants selling products or services on social media. The results showed that although use of online payment systems was universal among the respondents, most used direct money transfers, and only 18% of participants used PromptPay. Security, effort expectation, and social influence have a statistically significant influence on the intention to use PromptPay, whereas privacy and performance are not significant factors. These findings could particularly inform efforts by Thailand’s government and banks to ensure that online retailers feel confident adapting this service into their payment systems.